The involvement of serotonergic mechanisms in the antinociceptive effect of metformin - Lasica, Andjelka; Tomić, Maja; Nastić, Katarina; Pecikoza, Uroš; Micov, Ana; Stepanović-Petrović, Radica (Archives of Pharmacy, 2022)
Metformin, a well-known antidiabetic drug, has been shown to possess analgesic properties in inﬂammatory pain models, but the mechanisms of its antinociceptive effects are not completely understood. We aimed to examine the involvement of serotonergic mechanisms in metformin-induced antinociception in a model of inflammatory pain, using the formalin test in mice. Firstly, we examined the antinociceptive effects of intraperitoneally administered metformin in the first and second phase of the test. Then, the involvement of serotonergic receptors was evaluated by intraperitoneally pretreating mice with a 5-HT1B/1D (GR127935) or 5-HT1A receptor antagonist (WAY100635). Further, we examined the effect of metformin after depletion of endogenous serotonin with a tryptophan-hydroxylase inhibitor (PCPA; applied intraperitoneally for 4 days). Additionally, to avoid misinterpretation of motor incoordination, we performed the rotarod test with the highest tested metformin dose. Metformin (50-200 mg/kg) produced significant and dose-dependent antinociceptive effects (17-81%) in the second (inflammatory) phase of the test. Pretreatment with antagonists significantly reduced the antinociceptive effect of metformin (150 mg/kg). GR127935 inhibited the effects of metformin by 67% (1 mg/kg) and 100% (3 mg/kg), whereas the inhibitory effects for WAY100635 were 19% (1 mg/kg) and 68% (3 mg/kg). Depletion of serotonin with PCPA (100 mg/kg/day) significantly reduced the antinociceptive effects of higher metformin doses (150 and 200 mg/kg). Metformin (200 mg/kg) had no influence on rotarod performance. This study demonstrates that 5-HT1B/1D and 5-HT1A receptors are involved in metformin’s antinociceptive effects and that metformin’s action on these receptors seems to be indirect (mediated by endogenous serotonin released by metformin).